PENETAPAN KADAR ALKOHOL PADA ARAK JOWO YANG BEREDAR DI PONOROGO DENGAN METODE DESTILASI - Endang Ernawaningtyas; Devita Yudhayanti (Universitas Pesantren Tinggi Darul Ulum, 2017)
ABSTRACT Today, using Arak Jowo was really pathetic. It was very dangerous because it can lead to disruption for the perpetrators and the environment, such as unrest in the community. This research aim to determined alcohol concentration in Arak Jowo. The method used in this research was qualitative research experiment with Arak Jowo as object circulating in Ponorogo region in the period from January 2015 to April 2015. The sample was 8 bottles. The place of research in the laboratory of Akafarma Sunan Giri Ponorogo.arak jowo circulating in Ponorogo region is evidence police confiscated Ponorogo region. The sampling technique was random sampling 8 bottles of arak jowo. This research proven that arak jowo contain alcohol class B as many as four samples: samples No.1. 17.40% ethanol content, the sample No.4.14.98% ethanol content, the sample No. 5 19.29% ethanol content, ethanol content sample No.7. 13.16%. While the other four samples including alcoholic beverages in Class C is the sample No.2. ethanol 21.84%, sample No.3. 30.80% ethanol content, the sample No.6.23.20% ethanol content, the sample No.8. 21.28 % ethanol content. Keywords : arak jowo, alcohol, destilation